Graphite/ZnO nanorods junction for ultraviolet photodetectors. (March 2015) - Yatskiv, R.; Grym, J.; Verde, M.
Highlights: A simple and low-cost procedure for the fabrication of nanostructured ZnO UV photodetectors is reported. Structural and electrical properties of graphite-based Schottky structures on hydrothermally grown ZnO nanorods are discussed. Mechanism of photoresponse is outlined. Abstract: We report the fabrication of a graphite/ZnO nanorods (NRs) junction, which can act as a high-sensitivity ultraviolet (UV) photodetector, prepared by deposition of colloidal graphite on top of ZnO nanorod arrays obtained by low temperature hydrothermal growth. The photodetector is shown to be highly sensitive in a wide range of UV illumination intensities.